The foramen ovale from the fetal to neonatal life span - Wójtowicz-Marzec, Monika (Pediatria Polska - Polish Journal of Paediatrics, 2021)
The foramen ovale is an important structure that ensures the functioning of the fetal circulatory system. The work describes process of atrial septum formation from the embryonic stage to the neonatal period. Human atrial septation is inefficient process resulting in a persistent foramen ovale in quarter of adult population. Imaging of the foramen ovale is a valuable parameter for the assessment of the fetal circulatory system with the possibility of capturing life-threatening conditions. The dynamic process of adaptation to extrauterine life is also reflected at the foramen ovale in the postnatal period. The persistent foramen ovale is usually clinically silent in the pediatric population, while in the perspective of adulthood it may be a factor contributing to thromboembolic stroke. The aim of this article is to describe the essential differences in the function of the foramen ovale in the fetal and neonatal period.